Tattimbet: Great Names of the Kazakh Steppe of the XIX century - Saktaganova, Z.G. (KSU publ., 2019)
This article is published as part of the implementation of the project «Analytical research on updating, developing scientifically based selection criteria and information support for the project» Great Names of the Great Steppe «at the Chokan Valikhanov Institute of History and Ethnology of the Ministry of Education and Science of the Republic of Kazakhstan. In this project, the study of the contribution of prominent figures to the formation of statehood, science and culture of the country is being updated. The personality of Tattimbet Kazangapuly, which is the object of research in this work, played a huge role in the development of the Kazakh musical culture of the XIX and XX centuries. This article discusses the biography of the great kyushi (composer), the factors that contributed to the formation of this great personality: the composer's family tree, family traditions, the influence of close relatives, the cultural and intellectual environment, that is, everything that contributed to the formation of the «Tattimbet phenomenon». At a young age, Tattimbet formed as a mature kyushi, a wonderful performer with an extensive repertoire. A lot of various legends went about the life of Tattimbet, some of them are given in the article. An original, talented, handsome young man with exquisite taste, brilliant wit, aristocracy in behavior, the young Tattimbet was a favorite of the public. All aspects of life attracted the attention of the authors: musical performance, the great composer's gift of kyushi, legends and traditions associated with this area of life and creativity. Particular emphasis is placed on the administrative activities of Tattimbet, as the volost ruler of the Nurbike-Shansharovskaya volost of the Karkaraly district in 1842–1854, famous for its high moral qualities, justice, and the ability to help others. It also touches on the role of Tattimbet in the exploration of the mineral resources of Sary-Arka, as an unrivaled expert on the ore deposits of his region. The article is written on a complex of various materials: published research and journalistic works about the Kazakh kyusha; archival documents, family traditions and memories of the descendants of Tattimbet and others are involved. Opinions of researchers about the years of birth and death of the composer are given, which to this day remain designated as versions of various authors.
Keywords: Tattimbet; great names; Kazakh steppe; Sary-Arka; Kazakh society; culture